Development today; a new look at U.S. relations with the poor countries. - Hunter, Robert Edwards; Rielly, John E. (New York, Praeger, 1972)
This book is on the world development.
"Published in cooperation with the Overseas Development Council."
Bibliography: p. 275-279.
oo 12/8/18
Loans
Keywords: Economic assistance, American; Developing countries; United States